Ontogenetic variation of phyllotaxis and apex geometry in vegetative shoots of Sedum maximum (L.) Hoffm. - Dorota Kwiatkowska; Joanna Florek-Marwitz (Acta Societatis Botanicorum Poloniae, 2014)
Phyllotaxis of vegetative shoots of Sedum maximum (L.) Hoffm. is variable and unstable. Phyllotactic transitions proceeding either between two whorled, two spiral or a whorled and a spiral pattern occur during shoot ontogeny. A general rule is that in the course of these transitions numbers of contact parastichies increase or much less often diminish. During most common transitions only a single parastichy is added to or subtracted from the already existing contact parastichy pattern. This applies both to the transitions between a spiral and a whorled and to those between two spiral patterns. More parastichies appear only when phyllotaxis changes from one whorled pattern to another. These transitions, however, are the least common in S. maximum. Parameters of apex geometry differ significantly in shoots exhibiting different contact parastichy numbers. The sequence of phyllotactic patterns arranged according to an increasing apical dome area or area ratio, as well as decreasing plastochron ratio (both as defined by Richards) is the same as their sequence based on increasing numbers of contact parastichies. This in turn is the sequence of patterns as they appear during shoot ontogeny. The only parameter which remains relatively constant is the area of the youngest leaf primordium. This implies that during phyllotactic transitions in S. maximum the area ratio changes mainly due to the increase of the apical dome. It seems that in S. maximum this ontogenetic increase of the apical dome, which on the other hand is typical for many plants, somehow differs from these cases where such a change alters only contact parastichy numbers within the same phyllotactic series.